Anti-Phosphatidylserine/Prothrombin Antibodies at Two Points: Correlation With Lupus Anticoagulant and Thrombotic Risk - Egri, Natalia; Bentow, Chelsea; Rubio, Laura; Norman, Gary L.; López-Sañudo, Susana; Mahler, Michael; Pérez-Isidro, Albert; Cervera, Ricard; Viñas, Odette; Espinosa, Gerard; Ruiz-Ortiz, Estíbaliz (Frontiers in Immunology, 2021)
Antibodies to phospholipids (aPL) and associated proteins are a hallmark in the diagnosis of antiphospholipid syndrome (APS). Those included in the classification criteria are the lupus anticoagulant (LA) and the IgG and IgM isotypes of anticardiolipin (aCL) and anti-beta-2 glycoprotein I (β2GPI), antibodies. Non-classification criteria markers such as autoantibodies that recognize the phosphatidylserine/prothrombin (aPS/PT) complex have been proposed as biomarkers for APS. Studies of aPS/PT antibodies have shown strong correlation to clinical manifestations and LA. We aimed to study the value and the persistence of aPS/PT IgG and IgM antibodies in a cohort of consecutive patients with clinical suspicion of APS. Our study demonstrates that persistently positive results for aPS/PT IgG Ab were significantly associated with APS classification, thrombosis, triple aPL positivity, LA positive result, and Global APS Score (GAPSS)  than 9 points. On the other hand, no association was seen with pregnancy morbidity and SLE. Persistence of aPS/PT antibodies, defined according to the current laboratory classification criteria, likely improved diagnosis and clinical assessment of patients with APS.